ANALISIS PENGARUH KAPABILITAS MANAJERIAL TERHADAP PENINGKATAN KUALITAS LABA DAN NILAI PERUSAHAAN (Studi Empiris Pada Hotel The Ritz Carlton Nusa Dua – Bali) - Wayan Tantra; Gusti Ayu Mahanavami; Wiryawan Suputra Gumi; Niki Royke Kelejan (JUIMA : JURNAL ILMU MANAJEMEN, 2022)
This study aims to analyze the effect of managerial capability on improving earnings quality and firm value at The Ritz-Carlton Hotel, Nusa Dua – Bali. The variables used in this study are firm efficiency, free cash flow, firm value. The sample of this research was carried out by taking all the company's quarterly financial report data published by the Ritz-Carlton Hotel during the 2015-2019 period. Data analysis techniques used in this study: (1) multiple linear regression analysis with control variables, (2) moderated multiple linear regression analysis. The results of this study indicate that managerial capability has a significant effect on earnings quality. Managerial capability has a significant effect on firm value. Earnings quality has a significant effect on firm value. Earnings quality moderates the effect of managerial capability on firm value.